Rapid formation of an ice doline on Amery Ice Shelf, East Antarctica - Philipp S. Arndt; Roland C. Warner; Helen A. Fricker; Susheel Adusumilli; Jonathan Kingslake; Julian J. Spergel (Zenodo, 2021)
Data and code for: Warner, R., Fricker, H., Adusumilli, S., Arndt, P., Kingslake, J., & Spergel, J. (2021).Rapid formation of an ice doline on Amery Ice Shelf, East Antarctica. Funders: National Aeronautics and Space Administration Grant Number: NASA ICESat-2 ST Award No. 80NSSC20K0977 Recipient: Helen A. Fricker / National Aeronautics and Space Administration Grant Number: NASA Earth and Space Science Fellowship (NESSF) Award No. 80NSSC18K1424 Recipient: Susheel Adusumilli / National Aeronautics and Space Administration Grant Number: Future Investigators in NASA Earth and Space Science and Technology (FINESST) Award No. 80NSSC20K1666 Recipient: Philipp Sebastian Arndt / National Science Foundation Grant Number: National Science Foundation Grant No. OPP-1743310 Recipient: Julian Jacob Spergel / National Science Foundation Grant Number: National Science Foundation Grant No. OPP-1743310 Recipient: Jonathan Kingslake